The tiny giants of regeneration: MSC-derived extracellular vesicles as next-generation therapeutics - Zhang, Tianhe; Zhang, Liang; Ma, Xiaoxue; Song, Wenliang (Frontiers in Cell and Developmental Biology, 2025)
Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are revolutionizing the field of regenerative medicine, becoming the core carriers of next-generation acellular therapeutic strategies. In contrast to traditional mesenchymal stem cell therapy, these nanoscale “regenerative tiny giants” offer significant advantages, including low immunogenicity, efficient biological barrier penetration, and stable storage. As natural bioactive molecular carriers, MSC-EVs precisely regulate the inflammatory response, angiogenesis, and tissue repair processes in target tissues by delivering functional RNA, proteins, and other signaling elements. They have demonstrated multidimensional therapeutic potential in diseases such as bone and joint regeneration, nerve function reconstruction, myocardial repair, and skin wound healing. Worldwide, 64 registered clinical trials have preliminarily validated the safety and applicability of MSC-EVs across various diseases. Notably, they have shown significant progress in treating severe coronavirus disease 2019 (COVID-19), ischemic stroke, and complex wound healing. However, the lack of standardization in production processes, insufficient targeting for in vivo delivery, and the scarcity of long-term biodistribution data remain core bottlenecks limiting the clinical translation of MSC-EVs. Future interdisciplinary technologies, including 3-dimensional (3D) dynamic culture, genetic engineering, and intelligent slow-release systems, are expected to facilitate the transition of MSC-EVs from the lab to large-scale applications. This shift may transform “injectable regenerative factors” into “programmable nanomedicines”, offering new solutions for precision medicine.